What factors could influence physicians' management of women of childbearing age with chronic inflammatory disease? A systematic review of behavioural determinants of clinical inertia - Catherine Nelson-Piercy; Ivo Vlaev; Katie Harris; Rebecca Fischer-Betz (BMC, 2019)
Abstract Background Pregnancy represents a complex challenge to clinicians treating women with chronic inflammatory disease. Many clinicians face a situation of heightened sensitivity to the potential risks and uncertainties associated with the effect of pharmacological treatment on pregnancy outcomes. This may create an environment vulnerable to clinical inertia, whereby behavioural factors such as cognitive heuristics and biases, and other factors such as attitudes to risk and emotion can contribute. This systematic review was undertaken to assess if clinical inertia has been investigated/identified in this setting and took a behavioural science approach to identify and understand the potential determinants of clinical inertia in this treatment setting. Methods A systematic literature search was conducted to identify publications which investigated or described clinical inertia or its determinants (e.g. heuristics, biases etc.). Results were coded for thematic analysis using two inter-related behavioural models: the COM-B model and the Theoretical Domains Framework. Results Whilst studies investigating or describing clinical inertia in this treatment setting were not identified, the behavioural analysis revealed a number of barriers to the pharmacological management of women of fertile age affected by chronic inflammatory disease. Factors which may be influencing clinician's behaviour were identified in all domains of the COM-B model. The primary factors identified were a lack of knowledge of treatment guidelines and fears concerning the safety of medications for mother and fetus. Lack of experience of treating pregnant patients was also identified as a contributing factor to undertreatment. Conclusion Using a behavioural approach, it was possible to identify potential factors which may be negatively influencing clinician's behaviour in this treatment setting, although specific research was limited.